Experimental Study of Addition of Plastic Waste (PET) to the Shear Strength of Clay Soil - Irfan Ardiansah; Zainuri Zainuri; Muthia Anggraini (Litbang Pemas - Universitas Islam Lamongan, 2022)
Soil is a very important element in the success of a development project and is part of the foundation used. Therefore, stable soil is needed to obtain the required soil bearing capacity. Such as clay has the characteristics of low bearing capacity and large shrinkage. This study aims to determine the increase in the value of the shear strength of clay with the stabilization of PET plastic waste. The purpose of this study is to see the value of the shear strength of clay with variations in the amount of plastic waste 0%, 3.5%, 4%, and 4.5%. Method used is SNI 3420:2016 for the shear strength test. As a result, the addition of shredded plastic waste can increase the value of the shear strength of the soil.The value of shear strength increased at the percentage of plastic addition of 3.5% of 0.5663 kg/cm2 in the original soil test, the value of shear strength was 0.5271 kg/cm2, an increase of 7.43%. The conclusion is that there is an increase in the value of the shear strength of the soil stabilized by plastic waste at a variation of 3.5% of plastic waste, an increase of 7.43%.